Four amphi-Atlantic shrimps new for São Tomé and Príncipe (eastern central Atlantic) - Wirtz, Peter (2020)
The shrimps Thor amboinensis, Lysmata grabhami, Tuleariocaris neglecta, and Janicea antiguensis are recorded from São Tomé and Príncipe for the first time.